An evaluation of building sustainability considerations in South Africa : a case of the SAIAB building - Ngwadla, Xolisa (Rhodes University, Faculty of Commerce, Investec Business School, 2007)
The theory of sustainable development has received worldwide acceptance, and is characterised by the protection of environmental quality, social justice and economic development to ensure a quality of life for future generations. The concepts of sustainable development have transcended to all aspects of society, including the built environment through the Habitat Agenda and building sustainability rating tools. The thesis investigates the implications of sustainable development on how it relates to the building construction industry in South Africa. The study sought to evaluate the extent of consideration and motivation for the incorporation of sustainability criteria in building design, using the case of the South African Institute for Aquatic Biodiversity wet collection facility in Grahamstown. The goal of the thesis was achieved by evaluating sustainability considerations and barriers to adoption of sustainability criteria in the design of the SAlAB building, the rating of the building against the LEED â„¢ criteria, and evaluation of the applicability of the LEED â„¢ in the South African context. The importance of the research emanates from the fact that, despite the proliferation of sustainable development and sustainability rating tools in the world, there is no widely used building sustainability rating tool in South Africa, even though the country is industrialising with a very active built environment. The study therefore contributes to the body of knowledge necessary for the implementation of a building rating tool in the country, through an understanding of barriers to implementation. The research method used in the study was a case study with the intention of obtaining the design professional's considerations and challenges in the context of designing the SAIAB building. The case study used multiple data collection methods, with primary information obtained from interviews of professionals involved in the design of the building, whilst additional information was from analysis of technical drawings and review of literature on the subject. The findings of the research showed that there is an understanding of sustainability and consideration in the building industry even though there is no targeted intent to meet sustainability goals. The barriers to building sustainability were identified as lack of regulation, incentives, access to land, awareness, availability of professional codes and standards, economic costs and capacity. These barriers translated into a relatively low score, a silver rating for the SAlAB building when using the LEEDTM rating system. The implications of the findings suggests a need for the development of a comprehensive building sustainability rating tool suited for the South African context, with performance standards and a technical manual to support it. This should however be done in an environment where sustainability goals are supported by regulation and incentives have been developed.
Keywords: South African Institute for Aquatic Biodiversity; Construction industry -- Environmental aspects -- South Africa; Sustainable buildings -- Environmental aspects -- South Africa; Sustainable buildings -- Design and construction -- South Africa; Leadership in Energy and Environmental Design; Green Building Rating System